Interpreting the transparency as a communicative action in the Jurgen Habermas perspective - Nugraheni, Yuli; Ryadi, Agustinus; Muljani, Benedicta D. (P.A. Persona e Amministrazione, 2023)
This research explains the value of transparency of communication culture in the Surabaya Children's Community. This research is based on Jürgen Habermas's Communication Action Theory which interprets things rationally. It refers to the rationality that precedes the thesis, which asserts that communication will inevitably occur. The study uses qualitative research with the Focus Group Discussion method in the Surabaya community, known as Arek Suroboyo. The research results show that rational communication happens only when there is an understanding with at least one person. Communicatively, the occurring transparency value in the community exists in every individual's moment, development, and emancipation phenomena.